Profil smk negeri 3 solok ditinjau dari standar sarana dan prasarana pendidikan - Murwaldi Murwaldi; Anisah Anisah (Universitas Negeri Padang, 2022)
This research intends to obtain a comparison of the standard of facilities and infrastructure of SMK Negeri 3 Solok with Permendiknas number 40 of 2008. The comparison of facilities and infrastructure is reviewed from several aspects, namely land, buildings and the completeness of educational facilities and infrastructure. The research questions as follows are 1) how is the suitability of the land in SMK Negeri 3 Solok with the standards of existing facilities and infrastructure, 2) how is the suitability of the buildings in SMK Negeri 3 Solok with the standards of existing facilities and infrastructure, and 3) how is the suitability of completeness of existing educational facilities and infrastructure at SMK Negeri 3 Solok with the standard of existing facilities and infrastructure. The population of this research amounted to 451 people and a sample of 51 people with sampling using proportional simple random sampling technique. Data collection techniques using interviews, observation and documentation. Where the interviews were conducted by asking the contents of the guidelines for the table of contents that the author had prepared. The data analysis technique in this study is to compare the results of observations, checklists based on interviews and documentation that the author has done. The results of the study concluded that the building area of the land area is as much as 70% with the presence of some vacant land. The height of the school building is 28 m, which meets the maximum requirements for a building as high as 30 m. The condition of the floor of the SMK N 3 Solok building is in the good category. The school's distance from highways, rivers, railroads, and high-voltage channels is quite safe. the distance between the school and the equivalent building behind or beside the school building is considered safe with a distance of approximately 10 m. Meanwhile, for the completeness of the infrastructure there are still not in accordance with the standards, such as the prayer room that does not function properly, the UKS room and student organization rooms are not yet available, the counseling room is still temporary, and the number of bathrooms for female students whose ratio does not match the number of students. students and also spacious for the practice space of the three majors at SMK Negeri 3 Solok.